Effect of calcium hydroxide on fresh state behavior of sodium carbonate activated blast furnace slag pastes - Akturk, Busra; Kizilkanat, Ahmet B.; Kabay, Nihat (ELSEVIER SCI LTD, 2019)
This study represents the fresh state behavior of Na2CO3-activated ground granulated blast furnace slag (GGBS) pastes. Sodium carbonate (NC) is a suitable activator, though with an extended setting time. To accelerate the hydration process, NC was replaced with sodium hydroxide (NH), then, slaked lime (CH) was used as a carbonate binding agent. This replacement improved the rheological properties, but increased the setting time. The use of 3% CH with GGBS caused a significant decrease in setting time, enabled to set within 6.5 h. The decrement was attributed to the removal of a large amount of dissolved carbonate ions from the fresh state pastes. The NH replacement did not effectively enhance the fresh properties. In the pore solution, the CO32- ion concentration is one of the major parameter that affects the reaction besides other ions released from raw material. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Alkali activated materials; Sodium carbonate; Slag; Calcium hydroxide; Fresh properties; Carbonate concentration; MECHANICAL-PROPERTIES; PORE SOLUTION; ALKALINE ACTIVATION; REACTION-KINETICS; WASTE GLASS; CEMENT; RHEOLOGY; HYDRATION; STRENGTH; CONCRETE; Construction & Building Technology; Engineering; Materials Science